2001
DOI: 10.1002/1522-2675(20010321)84:3<579::aid-hlca579>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity in the Cycloaddition of Cyclopentadiene toN-Fumaroyl-[2R,S(R)]-Bornane-10,2-sulfinamide Monomethyl Ester

Abstract: The cyclic [2R,S(R)]-bornane-10,2-sulfinamide (À)-2b, an analogue of Oppolzers camphor-derived sultam (À)-2a, was synthesized by reduction of the known N-alkylidenesulfinamide ()-1b with NaBH 4 . The uncatalyzed [4 2] cycloaddition of cyclopentadiene to the methyl ester (À)-3b of the N-fumaroylsulfinamide, obtained from (À)-2b, proceeds with lower endo and p-facial selectivity as compared to dienophiles (À)-3a, c. In contrast to these latter, the diastereoselectivity is reversed either in apolar CCl 4 or in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Y. Sugihara and J. Nakayama envisioned, that despite steric hindrance syn-and anti-9,9'-dibenzonorbornenylidenes (128) seemed to be a convenient reagent for [2 + 2]-cycloaddition reaction with tosyl sulfinylaniline. Indeed, this allowed construction of a 1,2-thiazetidine scaffold upon prolonged refluxing in 1,2-dichloroethane.…”
Section: The [2 + 2]- [3 + 2]- and [4 + 2]-cycloaddition Reactions (E...mentioning
confidence: 99%
“…Y. Sugihara and J. Nakayama envisioned, that despite steric hindrance syn-and anti-9,9'-dibenzonorbornenylidenes (128) seemed to be a convenient reagent for [2 + 2]-cycloaddition reaction with tosyl sulfinylaniline. Indeed, this allowed construction of a 1,2-thiazetidine scaffold upon prolonged refluxing in 1,2-dichloroethane.…”
Section: The [2 + 2]- [3 + 2]- and [4 + 2]-cycloaddition Reactions (E...mentioning
confidence: 99%
“…v) NH 4 OH, dioxane, 208; 69%. This conformation also avoids a stereoelectronic destabilizing syn-periplanar orientation of both N/S lp [7]. vii) NaBH 4 , MeOH, H 2 O, 208; 90%.…”
mentioning
confidence: 95%
“…Its ability to generally induce high diastereoselectivity at the C(a)-atom of N-(a,b-unsaturated acyloyl) derivatives was rationalized by Kim and Curran on the basis of a steric argument, in which the approach is directed by the C(3) substituent in the chelated syn-s-cis conformation or by the pseudo-axial O(1)S substituent for the nonchelated anti-s-cis conformer [3]. In addition, by comparing structurally analogous dienophiles derived from (À)-1a and (À)-2a [7], we also demonstrated that the anti-s-cis vs. anti-s-trans equilibrium, hence the global diastereoselectivity, were strongly influenced by the pseudo-equatorial O(2)S substituent. Based on results from [4 2] cycloadditions [4] [5] or syn-dihydroxylations [6], we later completed this steric model by hypothesizing the concurrent high reactivity of the syn-s-cis conformer under uncatalyzed conditions [4].…”
mentioning
confidence: 99%
“… When a dienophile possessing a modified chiral sulfonamide auxiliary lacking the pseudoequatorial S=O was used for a Diels – Alder cycloaddition, TiCl 4 chelation with the pseudoaxial S=O resulted in total inversion of the π ‐facial selectivity . It is noteworthy that RMgX/Cu(I) and Gilman reagents (R 2 CuLi · PBu 3 ) both induce the same π ‐facial selectivities in both C β and concomitant electrophilic C α additions for very similar Michael acceptors .…”
mentioning
confidence: 99%